User Education in Libraries: An Analysis of Strategies, Objectives, and Implementation in the Digital Era - Rani Kurnia Vlora; Amalia Shaleha (Codex: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
User education in libraries plays a vital role in developing information literacy and users’ ability to effectively access and utilize information resources in the digital era. This study aims to analyze the objectives, strategies, implementation, and challenges of user education across various types of libraries in Indonesia. The research employed a library research method with an integrative narrative approach designed to synthesize previous studies and conceptual findings. Data were collected from reputable national and international journals, academic books, policy reports, and official publications from 2019–2025. A systematic search was conducted using databases such as Google Scholar, Scopus, and DOAJ, followed by content and thematic analysis to identify key patterns and research gaps. The results indicate that user education has evolved from basic service orientation into adaptive, interactive, and collaborative digital learning. Online, hybrid, and interactive media strategies have enhanced user engagement but remain challenged by limited resources and weak curricular integration. This study contributes to reinforcing the paradigm of user education as a core instrument in advancing information literacy and developing inclusive, sustainable digital library management.